Abundance of Probiotics and Butyrate‐Production Microbiome Manages Constipation via Short‐Chain Fatty Acids Production and Hormones Secretion. Issue 23 (22nd October 2019) - Zhuang, Min; Shang, Wenting; Ma, Qiuchen; Strappe, Padraig; Zhou, Zhongkai
Abstract : Scope: The characteristics of gut microbiota and host metabolism are hypothesized to be associated with constipation status, but the regulation mechanism is not fully understood. Thus, the current study investigates the effect of constipation symptoms on gut functionality following the modulation of gut microbiota and metabolites via dietary fiber intervention. Methods and results: Constipation causes a significantly reduced short‐chain fatty acids (SCFAs) production and a higher level of iso‐butyrate. The feces of constipated people are characterized with inhibited Faecalibacterium, Ruminococcaceae and Roseburia abundance. Desulfovibrionaceae is identified to be an important endotoxin producer in constipated patients, and a butyrate‐enriched SCFAs profile achieved by dietary fiber supplement accelerates gastrointestinal transit and increases the thickness of the mucosal layer, possibly through triggering the secretion of colonic hormones and enhancing the expression of tight junction proteins for maintaining intestinal barrier integrity. More importantly, an interacting regulatory mechanism among SCFAs, in particular butyrate and propionate, may be involved in signaling between the microbiome and host cells in the colon. Conclusion: Gut microbiota, characterized with enriched butyrate‐producing and depressed Desulfovibrionaceae bacteria, attenuates constipation symptoms through promoting intestinal hormones secretion and maintaining gut barrier integrity. Abstract : Probiotics and butyrate‐producing microbiome attenuate constipation by promoting short‐chain fatty acids (SCFAs) production and hormone secretion. The feces of constipated patients have lower SCFAs and the butyrate‐enriched SCFAs profile triggers colonic hormone secretion for maintaining intestinal barrier integrity. Gut microbiota, characterized with promoted butyrate‐production bacteria and Lactobacillus, benefit constipation. Concentration and proportion of SCFAs seem to be the key factors involved in constipation attenuation.